Vietnam Affordable Housing : A Way Forward - World Bank Group (World Bank, Washington, DC, 2015)
Affordable housing will be instrumental to helping Vietnam achieve its goals for increasing productivity and inclusive urban growth. Since Doi Moi, the country has experienced impressive economic growth, averaged at 7.4 percent per annum from 1990 to 2008, lowering to an average of 6 percent per annum from 2007 to 2013. Strong economic growth has supported a substantial reduction in poverty, from 58 percent in 1993 to 17 percent in 20121. Yet, the country has remained largely rural, with more than half of its population working in the agricultural sector, which only contributed 17 percent of GDP in 20142. In some countries, urbanization has been used as a tool to accelerate economic growth and poverty reduction. As Vietnam aims to maintain a high growth rate, supporting urbanization, where cities contribute a growing share of jobs and GDP, will be an important measure. This structural shift will drive population growth and new demand for housing in cities, for which quality and affordable housing options in well-serviced and connected settlements will be needed. Areas of particular importance in the Law is support toward self-built housing, the active participation of the private sector, addressing the shortage of affordable rental housing as well as high demand for housing from low income groups, especially workers in industrial zones of large cities. This report, which includes a comprehensive assessment and roadmap for affordable housing in Vietnam, recommends the following key messages moving forward: increase investment, Prepare Three Flagship Initiatives under an umbrella National Affordable Housing Program, Institutional Strengthening, Land Tax Reform, and Create an Enabling Environment for Affordable Housing. Moving forward, design of the market-oriented measures described above will require intensive and careful consultation and engagement with all housing sector actors, particularly the private sector. Private sector will need to play an active role in the early preparation to ensure their participation and commitment that carries through to implementation of policy measures on the financing and supply side.